Hypersensitive or Detrusor Overactivity: Which is Associated with Filling Symptoms in Female Bladder Outlet Obstructed Patients? - Zhang, Junlong; Cao, Mingxin; Chen, Yu; Liang, Weijie; Liang, Yueyou (Urology Journal, 2019)
Purpose: To investigate and compare detrusor overactivity (DO) and bladder filling sensation characteristics in female bladder outlet obstruction (FBOO) patients with or without overactive bladder (OAB) symptoms. Materials and Methods: One hundred fifty-seven FBOO patients with urodynamic testing were recruited. Patients who showed urinary urgency ( ? 6 episodes/3 d), with or without urinary frequency ( ?8 voids/24 h), and urge incontinence ( ? 3 episodes/3 d) were considered to have OAB. The detrusor overactivity (DO) and bladder filling sensation measures including first sensation (FSF), first desire to void (FDV) and strong desire to void (SDV) during filling cystometry were recorded. The associations between urodynamic variables and OAB symptoms were analysed. Result: FBOO patients had a high incidence (79%) of OAB. FBOO patients with OAB symptoms had significantly younger age, higher incidence of DO (19.4% versus 6.1%) (P = .051) and lower bladder volumes of FSF (180.32 ± 83.48 versus 226.18 ± 100.90 mL), FDV (269.00 ± 109.78 versus 330.45 ± 123.95 mL) and SDV (345.56 ± 135.43 versus 422.33 ± 148.40 mL) (P < .05) compared to patients without OAB. In multivariate analyses, both DO (OR = 4.83, 95% CI: 1.02-22.85, P = .047) and lower bladder volumes at FDV(OR = 2.47, 95% CI: 1.03-5.95, P = .044) and SDV (OR = 3.07, 95% CI: 1.25-7.55, P < .014) were still independently associated with OAB, after adjustment for age and other confounding factors. Conclusion: FBOO patients had a high incidence of OAB. Not only DO but also bladder hypersensitivity were independently associated with OAB symptoms in FBOO patients.